Shifting of the Ganga and land erosion in West Bengal - Rudra, Kalyan (Calcutta, 2006)
The present study offers an excellent analysis of the limitations of traditional engineering approach to water management and reinforces the urgent need for a new and holistic knowledge base, if India has to develop and utilize its river systems in a sustainable manner.
Keywords: Environment